ENGLISH PHONETIC PROBLEMS. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines common phonetic problems encountered by learners of English as a second or foreign language. It explores the linguistic and psychological roots of these issues and reviews effective pedagogical strategies to address them. The article is structured with a comprehensive introduction, literature analysis, methodology, results, discussion, and final suggestions. Emphasis is placed on segmental and suprasegmental difficulties, native language interference, and effective pronunciation instruction methods.